2017
DOI: 10.1371/journal.pcbi.1005377
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial separation of two different pathways accounting for the generation of calcium signals in astrocytes

Abstract: Astrocytes integrate and process synaptic information and exhibit calcium (Ca2+) signals in response to incoming information from neighboring synapses. The generation of Ca2+ signals is mostly attributed to Ca2+ release from internal Ca2+ stores evoked by an elevated metabotropic glutamate receptor (mGluR) activity. Different experimental results associated the generation of Ca2+ signals to the activity of the glutamate transporter (GluT). The GluT itself does not influence the intracellular Ca2+ concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…One third of the single astrocyte models took into account neurotransmitters in a simplistic way just as a stimulus, having either the neurotransmitter as a constant, step function, or something similar (see e.g., Larter and Craig, 2005 ; Gibson et al, 2007 ; Bennett et al, 2008b ; De Pittà et al, 2009a ; Dupont et al, 2011 ; Toivari et al, 2011 ; Witthoft and Karniadakis, 2012 ; Hadfield et al, 2013 ; Witthoft et al, 2013 ; Kenny et al, 2018 ). Only two models (Chander and Chakravarthy, 2012 ; Oschmann et al, 2017 ) actually modeled the amount of neurotransmitter with a differential equation. The stimulus to the astrocyte model by Oschmann et al ( 2017 ) was taken from the model by Tsodyks and Markram ( 1997 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One third of the single astrocyte models took into account neurotransmitters in a simplistic way just as a stimulus, having either the neurotransmitter as a constant, step function, or something similar (see e.g., Larter and Craig, 2005 ; Gibson et al, 2007 ; Bennett et al, 2008b ; De Pittà et al, 2009a ; Dupont et al, 2011 ; Toivari et al, 2011 ; Witthoft and Karniadakis, 2012 ; Hadfield et al, 2013 ; Witthoft et al, 2013 ; Kenny et al, 2018 ). Only two models (Chander and Chakravarthy, 2012 ; Oschmann et al, 2017 ) actually modeled the amount of neurotransmitter with a differential equation. The stimulus to the astrocyte model by Oschmann et al ( 2017 ) was taken from the model by Tsodyks and Markram ( 1997 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been shown that the concentration of certain chemical species, such as Ca 2+ , can vary drastically in different parts of the cell (see e.g., Thul, 2014 ; Dupont et al, 2016 ), and several models took into account the spatiality by modeling diffusion of at least some of the chemical species in astrocytes using partial differential equations (PDEs, see e.g., Roth et al, 1995 ; Höfer et al, 2002 ; Bennett et al, 2008a ; Gibson et al, 2008 ; Allegrini et al, 2009 ; Kang and Othmer, 2009 ; Edwards and Gibson, 2010 ; Wei and Shuai, 2011 ; Li et al, 2012 ; López-Caamal et al, 2014 ; Mesiti et al, 2015a ; Yao et al, 2018 ). Some models took a simpler approach to spatiality by modeling ODEs combined with fluxes between different astrocytic compartments, such as cytosol and ER (see e.g., Larter and Craig, 2005 ; Di Garbo et al, 2007 ; Postnov et al, 2007 ; Lavrentovich and Hemkin, 2008 ; Di Garbo, 2009 ; Zeng et al, 2009 ; Amiri et al, 2011a ; DiNuzzo et al, 2011 ; Farr and David, 2011 ; Oschmann et al, 2017 ; Kenny et al, 2018 ). In addition of modeling Ca 2+ fluxes between ER and cytosol, Silchenko and Tass ( 2008 ) modeled free diffusion of extracellular glutamate as a flux.…”
Section: Methodsmentioning
confidence: 99%
“…The computation of the NCX strength was based on the obtained experimental data obtained here and according to an earlier study (Oschmann et al, 2017) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…8A). These were fed into an equation describing the current strength of the NCX as described previously (Oschmann et al, 2017). Figure 8B shows that, in this model, NCX current is inward under baseline conditions (i.e., in the sodium import/calcium extrusion mode).…”
Section: Nmda-induced Ion Signaling and Ncx Activitymentioning
confidence: 99%
“…However, the Ca 2+ entry through the VGCCs may still need to be amplified by CICR (Carmignoto, Pasti, & Pozzan, 1998). Na + /Ca 2+ exchanger (NCX) can transport Ca 2+ into the astrocytes upon increase in intracellular Na + concentration which occurs during glutamate uptake (Brazhe, Verisokin, Verveyko, & Postnov, 2018;Oschmann, Mergenthaler, Jungnickel, & Obermayer, 2017;Rojas et al, 2007). Other sources of the Ca 2+ entry in astrocytes include store-operated channels ORAI1 and transient receptor potential type A channels (TRPAs) (Bazargani & Attwell, 2016;Shigetomi, Jackson-Weaver, Huckstepp, O'Dell, & Khakh, 2013).…”
mentioning
confidence: 99%